Epidemiology of confirmed coronary heart disease among population older than 60 years in rural central India—A community-based cross-sectional study - Sheetal Bodkhe; Sumedh U. Jajoo; Ulhas N. Jajoo; Sheetal Ingle; Subodh S. Gupta; Bharati A. Taksande (Indian Heart Journal, 2019)
Background: Three-fifths of total deaths in India are attributed to noncommunicable diseases, and coronary heart disease (CHD) is one of the dominant causes. There are only few studies available in India to find confirmed CHD by pragmatic approach. This study aims to find prevalence of confirmed CHD and its risk factors in rural community of central India. Materials and methods: This was a community-based cross-sectional study during 2013–2014 involving adults ≥60 years from 13 villages in rural central India. We screened CHD on the basis of history and standard 12-lead ECG. Apart from the past documentation of CHD, we diagnosed confirmed CHD in symptomatic patients or with resting ECG changes by means of echocardiography, exercise ECG test or coronary angiography whenever needed. Results: We screened 1190 of 1415 individuals ≥60 years for CHD. Five hundred eighty were men and 610 were women. Diagnosis of CHD was confirmed in 61 individuals (29 men and 32 women). The prevalence of CHD in individuals older than 60 years was 51.3 per 1000 population. Hypertension was the only independent risk factor associated with CHD, whereas association of diabetes mellitus, obesity, socioeconomic status and smoking with CHD was not significant. Conclusion: Prevalence of confirmed CHD has increased in agrarian rural community in central India, which requires further studies to find out causative factors. Keywords: Coronary heart disease, Epidemiology, Rural India